2004
DOI: 10.1021/la0490902
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Microcapsules Containing Two-Phase Core Materials

Abstract: Urea-formaldehyde (UF) microcapsules containing two-phase core materials in which phthalocyanine blue BGS (beta-CuPc) particles were homodispersed in tetrachloroethylene (TCE) were prepared by in situ polymerization. The effects of the various process parameters, including the type of surface modifier, the viscosity of UF prepolymer, the type of water-soluble surfactant, and the concentration of oil-soluble surfactant in the capsule core on the dispersity of beta-CuPc particles in TCE and the properties of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…6, the pentoxifylline release was the highest at the emulsifier content of 2.0%, while this at the emulsifier content of 1.0%, 2.0% and 2.5%, was lower. The reason should be that the average particle size of the microcapsules at the emulsifier content being 2.0% is the smallest, while those from the microcapsules at the emulsifier content being 1.0%, 1.5% and 2.0 % are larger, and the smallest particle size microcapsules would have the largest total specific surface area, therefore causing the highest release at the same temperature and pH 29 . …”
Section: Effect Of Ph On the Drug Release Behaviour Of Microcapsulesmentioning
confidence: 99%
“…6, the pentoxifylline release was the highest at the emulsifier content of 2.0%, while this at the emulsifier content of 1.0%, 2.0% and 2.5%, was lower. The reason should be that the average particle size of the microcapsules at the emulsifier content being 2.0% is the smallest, while those from the microcapsules at the emulsifier content being 1.0%, 1.5% and 2.0 % are larger, and the smallest particle size microcapsules would have the largest total specific surface area, therefore causing the highest release at the same temperature and pH 29 . …”
Section: Effect Of Ph On the Drug Release Behaviour Of Microcapsulesmentioning
confidence: 99%
“…% of 1-octadecanol as a nucleating agent. Wang et al [29] fabricated Urea-formaldehyde (UF) microcapsules containing two-phase core materials in which phthalocyanine blue BGS particles were homo-dispersed in tetrachloroethylene (TCE).…”
Section: In Situ Polymerizationmentioning
confidence: 99%
“…The charged properties were tested on modified particles at different pH values, and the results indicated that particles at pH <10 responded to electric field and the response time decreased with pH increasing from 50 s (pH 1-2) to 35 s (pH [8][9]. No response was found at pH 12-13, assuming that less quantity of H 2 SO 4 could not fully react with NaAlO 2 at high pH.…”
Section: Effect Of Temperature On Modificationmentioning
confidence: 99%